1981
DOI: 10.1007/bf00135106
|View full text |Cite
|
Sign up to set email alerts
|

Meiosis in hybrids between tree coffees (C. liberica, C. dewevrei) and Nandi coffee (C. eugenioides)

Abstract: Meiotic behaviour of hybrids between Coffea debr'evrei var. 'excelsa' and C. eugenioides, and between C. liberica and C. eugenioides, and of open pollinated progeny of these hybrids reveals a close genome relationship in spite of striking morphological differences and distinct geographic separation. In the cross C. dewevrei 'excelsa' X C. eugenioides several maternal types occurred, attributed to parthenogenesis.The hybrids are self-sterile and set few seeds on open pollination, again partly involving partheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Many of the irregularities reported in the process of meiotic division in this study were also found in other studies with coffee hybrids, such as C. racemosa and C. arabica (Medina 1963), C. arabica and C. kapakata (Mônaco and Medina 1965), C. dewevrei and C. eugenioides, C. liberica and C. eugenioides (Reddy and Narayan 1981), and C. arabica and C. canephora (4x) (Owuor 1985;Boaventura and Cruz 1987). Furthermore, some meiotic abnormalities observed in the F 2 population could also reflect the doubling of the single diploid C. canephora genome or incompatibility caused by genomic divergence between their parents.…”
Section: Unisupporting
confidence: 87%
See 1 more Smart Citation
“…Many of the irregularities reported in the process of meiotic division in this study were also found in other studies with coffee hybrids, such as C. racemosa and C. arabica (Medina 1963), C. arabica and C. kapakata (Mônaco and Medina 1965), C. dewevrei and C. eugenioides, C. liberica and C. eugenioides (Reddy and Narayan 1981), and C. arabica and C. canephora (4x) (Owuor 1985;Boaventura and Cruz 1987). Furthermore, some meiotic abnormalities observed in the F 2 population could also reflect the doubling of the single diploid C. canephora genome or incompatibility caused by genomic divergence between their parents.…”
Section: Unisupporting
confidence: 87%
“…Hybrids between the species C. arabica and C. canephora have been obtained on different occasions, and they are called "Arabusta" (Mendes 1950). Because of its importance, meiotic behavior had already been studied to some F 1 hybrids and also to parental plants in order to explore the genetic resources of these hybrids (Mendes 1950;Medina 1952;Medina 1963;Mônaco and Medina 1965;Medina and Rijo 1969;Reddy and Narayan 1981;Owuor 1985;Boaventura and Cruz 1987;Boaventura 1990).…”
Section: Introductionmentioning
confidence: 99%